2007
DOI: 10.1080/13693780601103098
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model of pharyngeal candidiasis with local symptoms characteristic of pharyngeal thrush produced by using an inhaled corticosteroid

Abstract: We established a novel murine model of pharyngeal candidiasis maintaining stable yeast population and local symptoms characteristic of pharyngeal thrush. The persistent Candida-infection was prolonged by inhalation of beclomethasone dipropionate corticosteroid. The severity of infection lesions was evaluated by determining viable cell number of Candia albicans and scores representing symptomatic curd-like white patch on pharyngeal tissue. The utility of this model was shown by the disappearance of lesions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We can assume that BDP exuded from the BDP-film facilitated colonization, perhaps through suppression of host defense mechanisms, based on our previous report 7) indicating that oral inhalation of BDP allows elongated deterioration of experimental pharyngeal candidiasis in mice. However, a glucocorticoid may suppress various types of host defense mechanisms against microbial infections; in this study we examined the effects on neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We can assume that BDP exuded from the BDP-film facilitated colonization, perhaps through suppression of host defense mechanisms, based on our previous report 7) indicating that oral inhalation of BDP allows elongated deterioration of experimental pharyngeal candidiasis in mice. However, a glucocorticoid may suppress various types of host defense mechanisms against microbial infections; in this study we examined the effects on neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…7) Here, we compared the effects of the attachment of BDP-containing film, topical application of BDPsuspension and subcutaneous administration of prednisolone. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we believe it is possible that the beneficial effects of farnesol on oral candidiasis may be limited locally. In this regard, we can note that oral or pharyngeal infection by Candida is easily influenced by local treatments with immunosuppressive agents, as our previous report indicated that oral inhalation of beclomethasone dipropionate degenerated the lesions of experimental pharyngeal candidiasis in mice (13).…”
Section: Discussionmentioning
confidence: 90%